Challenges in Implementing Islamic Religious Education Policies: An Institutional Theory Analysis - Rusydianti, Dian; Masyhar, Ali ‎; Miftah , Muhammad ‎ (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study examines the institutional implementation of Islamic Religious Education (IRE) in an Indonesian university context, focusing on the growing tension between formal regulatory compliance and the substantive realization of holistic character formation in contemporary higher education. Drawing on institutional theory, particularly the concept of institutional decoupling, the study employs a qualitative case study design using in-depth interviews, document analysis, and non-participant observation to investigate how IRE policy is structured, enacted, and adapted at Universitas Muria Kudus. The findings demonstrate a pattern of partial decoupling: although formal alignment with national mandates is evident through compulsory course allocation, standardized learning outcomes, and administrative structuring, these formal arrangements do not consistently translate into comprehensive affective and behavioral transformation. This gap is primarily shaped by structural constraints, notably limited credit hours and lecturer workload. At the same time, the study identifies adaptive institutional mechanisms—primarily structured co-curricular mentoring programs—that operate as re-coupling strategies connecting symbolic policy commitments with lived religious practice. These initiatives extend learning beyond classroom boundaries and enable more experiential internalization of ethical and spiritual values. The study concludes that meaningful IRE implementation requires hybrid governance models that integrate curricular and co-curricular structures and are supported by proportionate institutional resources. The findings imply the need to recalibrate policies on credit allocation, lecturer workload distribution, and the formal recognition of mentoring frameworks as strategic institutional instruments for character education, while extending the relevance of institutional decoupling analysis to religious education policy in higher education.